2023
DOI: 10.1159/000529194
|View full text |Cite
|
Sign up to set email alerts
|

Internalized Stigma in Hidradenitis Suppurativa: A Multicenter Cross-Sectional Study

Abstract: Background: Hidradenitis suppurativa (HS) causes significant physical, social, and psychological burdens. Internalized stigma, acceptance of negative attitudes and stereotypes of society regarding a person’s illness, has not been studied previously in HS. Objectives: To investigate the internalized stigma state of HS patients and identify the factors affecting it. Methods: This multicenter, prospective, cross-sectional study included 731 patients. Internalized Stigma Scale (ISS), Hurley staging, Physician Glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Hidradenitis suppurativa, characterized by painful, draining lesions of the axillae, inguinal, and inframammary areas, areas entirely concealed by clothing, had a high extent of perceived stigma in children. Hidradenitis suppurativa has also been shown to cause considerable perceived stigma in affected adults . Assessment of the relative role of perceived vs experienced stigma on a disease-specific basis relative to visibility and severity is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Hidradenitis suppurativa, characterized by painful, draining lesions of the axillae, inguinal, and inframammary areas, areas entirely concealed by clothing, had a high extent of perceived stigma in children. Hidradenitis suppurativa has also been shown to cause considerable perceived stigma in affected adults . Assessment of the relative role of perceived vs experienced stigma on a disease-specific basis relative to visibility and severity is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Jørgensen and colleagues 29 reported that the scores for each of the 10 question items in the DLQI increased significantly in line with Hurley Stages. Bilgiç and colleagues 30 investigated internalized stigma in a recent multicenter study from T ürkiye reported a mean DLQI score of 13.88 6 8.98 in 731 patients with HS. In the present study, the mean DLQI score was lower at 7.5 6 6.5.…”
Section: Discussionmentioning
confidence: 99%
“…Stigmatization may result in impaired body image perception 38 . Patients with HS internalize society's judgments, which could have a severe impact on their ability to access medical care 39 . In order to improve the quality of health care, it is crucial to address internalized stigma in addition to disease activity 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HS internalize society's judgments, which could have a severe impact on their ability to access medical care 39 . In order to improve the quality of health care, it is crucial to address internalized stigma in addition to disease activity 39 . A psychodermatological approach enhances QoL, disease flare-ups, and long-term management of the condition 40 .…”
Section: Discussionmentioning
confidence: 99%